Nursing students' learning commitment, self‐efficacy and grit during the COVID 19 pandemic: Quantitative empirical research on adaptation to college life - Juhyun Jin; Hyeran An (Wiley, 2023)
Abstract Aims To examine the learning commitment, self‐efficacy, grit and adaptation to college life among Korean nursing students, under the prolonged COVID‐19 situation, and identify the factors that affect their adaptation to college life. Design A cross‐sectional study. Methods The participants were 247 nursing students. The instruments used in the study were the Learning Commitment Scale for Adults, Self‐Efficacy Scale, Grit Scale and Campus Life Adaptation Scale (developed for Korean nursing students). A multiple linear regression analysis was conducted using SPSS 23.0. Results Adaptation to college life had significant positive correlations with learning commitment, self‐efficacy and grit. Moreover, self‐efficacy and learning commitment were key correlators for adapting to college life.